Evaluation of microstructure and mechanical properties of magnesium alloy based porous bone substitutes. (2022) - Garimella, Adithya; Ashri, Akshun; Kumar, Animesh; Kumar, Anupam; Ghosh, Subrata Bandhu; Bandyopadhyay-Ghosh, Sanchita
Highlights: FE-SEM results establish the presence of arbitrary interconnected pores of micro and macro sizes in the sample, which is a crucial feature of an ideal scaffold. EDX results depict the individual compositional weights of the samples and were found to be incoherent with the compositional details of samples, and presence of no foreign element was observed. Enhancement of mechanical properties were observed, due to the incorporation of alloying elements (Ca and Zn) into magnesium metal matrix. Although, the mechanical properties of the sample were noted be decreasing, as the porosity of the sample increased, yet found the values in the range of natural bone. Abstract: Orthopedic implants based on magnesium (Mg) have been found to be a prospective metallic biomaterial owing to its biocompatibility, biodegradability and similar mechanical properties with respect to natural human bone. However, owing to its accelerated degradation in physiological solution, application of pure Mg as implant material is limited. Besides, conventional metallic implants are non-porous and often lead to stress-shielding. To this end, this investigation has focused towards biomimicking the native human bone, by fabricating porous Mg alloy-based bone scaffolds. Mechanical properties were tuned by introducing calcium and zinc as alloying elements into Mg metal matrix. Uniform distribution of alloying elements, along with gradient porosity was observed by FESEM with EDX analysis. The developed porous samples were examined for mechanical performance, that revealed comparable and tunable mechanical properties similar to natural bone even after introduction of porosities, thereby signifying promising potential of the Mg-alloy based bone implants developed in this study.